Pajak Penghasilan Dividen dan Investasi Nasional: Tinjauan Yuridis UU Harmonisasi Peraturan Perpajakan - Andriyana, Hendra; Tjaraka, Heru (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The enactment of the Law on Harmonization of Tax Regulations (UU HPP) has changed the provisions for paying income tax by taxpayers, both in terms of double tax deductions, one-level tax systems and investment incentives. This research aims to analyze income tax on dividends within the legal framework of the HPP Law as well as the impact of implementing the HPP Law on the development of national investment. The research method used is a normative research method with a statutory and conceptual approach. The results of this research show that the implementation of the HPP Law as one of the government's steps in efforts to harmonize national tax regulations, one of which regulates income tax on dividends, has had various impacts, including reducing double taxation, simplifying the income taxation system, and supporting national investment. Implementing the HPP Law increases the interest of local and foreign investors to continue investing their business results domestically, both in the capital market and the real sector. It is supported by the publication of quantitative data from the Ministry of Investment/BKBM, where there is a positive trend in investment realization nationally in the first and second quarters of 2023.